4-methylesculetin, a coumarin derivative, ameliorates dextran sulfate sodium-induced intestinal inflammation - Witaicenis, Aline [UNESP] (2018)
4-methylesculetin is one of the coumarin derivatives with great anti-oxidant and anti-inflammatory activities. Recent studies have shown that 4-methylesculetin has a promising potentiality to treat inflammatory diseases, especially those related to reactive oxygen species, as inflammatory bowel disease. Based on this, the present study aims to investigate the intestinal anti-inflammatory activity of 4-methylesculetin in dextran sulfate sodium (DSS) model. For this purpose, mice received DSS 5% for 5 days followed by 2 days of filtered tap water. Treated groups received orally 5 or 25 mg/kg of 4-methylesculetin daily since the first day. Macroscopic, microscopic and biochemical parameters were evaluated. 4-methylesculetin (25 mg/kg) improved microscopic parameters, decreased MPO activity, reduced the colonic levels of IL-6 and counteracted GSH depletion when compared with DSS-control group. Our results show the intestinal anti-inflammatory activity of 4-methylesculetin in DSS model, which is related to its antioxidant and anti-inflammatory properties. This way, 4-methylesculetin, is a new potential compound for treatment of both types of IBD.